Cultural Preaching on Modern Society: A Phenomenological Study of an Islamic Foundation in Kudus - Ravida Chauria Shavir (Lentera: Jurnal Ilmu Dakwah dan Komunikasi, 2021)
Rapid changes in both rural and urban societies require da’wa to be delivered more creatively. This paper aims at investigating the development of cultural da’wa by analyzing the dynamics of socio-cultural life in an Islamic da’wa institution named Yayasan Pendidikan Islam Kyai Thelingsing (YPIKT). This paper applies a qualitative phenomenological approach. Finding reveals that the cultural da’wa approach to the urban community was manifested in three ways: education, cultural heritage (grave pilgrimage), and recitation. On the education aspect, the YPIKT has four levels. The cultural heritage is shown by Haul Mbah Kyai Thelingsing activity, which attended whether Muslim and non-muslim (Chinese descendent) every Muharram. The recitation aspect has an ultimate goal this activity is happened every day after Maghrib or every Thursday night by the name of tahlilan.Keywords: Da’wa, Cultural, Community, Modern, Education